Facile fabrication and characterization of polyimide nanofiber reinforced photocured hybrid electrolyte for Li-ion batteries - KAYAMAN APOHAN, NİLHAN (WILEY, 2017)
In this study, a novel ion conductive polyimide (PI) nanofiber reinforced photocured hybrid electrolyte has been fabricated. Polyimide fibers were fabricated with the reaction between 4,4-oxydianiline (ODA) and 3,3,4,4-benzophenonetetracarboxylic dianhydride (BTDA) followed by electrospinning and thermal imidization methods. Then, PI electrospun fibers were dipped into hybrid resin formulation containing bisphenol A ethoxylate dimethacrylate (BEMA), poly (ethylene glycol) methyl ether methacrylate (PEGMA) and 3-(methacryloyloxy) propyltrimethoxysilane (MEMO) and then photocured to prepare PI nanofiber reinforced electrolyte membrane. Photocured membranes were soaked into lithium hexafluorophosphate (LiPF6) before measuring electrochemical stability and ionic conductivity of hybrid polyelectrolyte. The chemical structure and electrochemical performance of the electrolytes were examined by Fourier transform infrared (FTIR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), electrochemical impedance spectroscopy (EIS), linear sweep voltammetry (LSV) and scanning electron microscopy (SEM) analysis. The incorporation of MEMO into organic matrix effectively increased the modulus from 2.83 to 5.91MPa. The obtained results showed that a suitable electrolyte for Li-ion batteries with high lithium uptake ratio, high conductivity (7.2x10(-3)S cm(-1)) at ambient temperature and wide stability window above 5.5V had been prepared. Copyright (c) 2017 John Wiley & Sons, Ltd.
Keywords: polymer membrane; polyelectrolyte; nanofiber; electrospinning; Li ion battery; INDUCED PHASE-SEPARATION; GEL POLYMER ELECTROLYTES; LITHIUM BATTERIES; NONWOVEN SEPARATORS; MEMBRANES; PERFORMANCE; STABILITY; TRANSPORT; DEVICES; CELLS